Mobile Application with Artificial Intelligence Chatbots for Dengue Information and Management - Menéndez Mueras, Rosa; Medina Rafaile , Esteban Julio; Herrera Salazar, José Luis (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Dengue fever has intensified in recent years, affecting millions, with an estimated 100 to 400 million people yearly; approximately 80% of these cases have been reported in the Americas. This develops a prototype of a mobile application that includes artificial intelligence (AI) chatbots for dengue management and information. The design thinking methodology was applied, which was useful due to its focus on user needs, allowing the identification of key problems in dengue management and the design of innovative and functional solutions. The results were validated by experts using criteria such as technology, innovation, and feasibility with an average score of 4.26 and users using criteria such as functionality, usability, and accessibility with an average score of 4.28, showing a high level of acceptance. This tool has the potential to improve early disease detection, facilitating data collection and real-time interaction with patients. Through the use of AI, the application aims to optimize case management, reduce serious complications, and support health systems in at-risk areas.